Implementation of Character-Based Holistic Education in Islamic Boarding School Educational Institutions - Faisol, Ahmad; baharuddin, Baharuddin; Padil, Moh; Barizi, Ahmad (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Current education has not fully paid attention to the development of students' personalities as a whole, with there still being a dichotomy between science, institutions, and educational concepts. Therefore, a holistic character education model is needed that integrates religious education with the general curriculum and emphasizes mastery of science and technology to produce students with character and develop as a whole. This study aims to analyze the concept, implementation, and impact of character-based holistic education in SMP Ar-Rohmah Islamic Boarding School (IBS) Malang. With a qualitative approach based on case studies, data was obtained through interviews, observations, and documentation, and analyzed using triangulation of data sources. The results of the study show that character-based holistic education at Ar-Rohmah IBS Junior High School includes: (1) Concepts formulated based on holistic education values as graduation standards; (2) Implementation consisting of three stages: planning (determining grades, teacher training, and providing facilities), implementation (integrating character values into lessons, methods, school programs, and communication between components), and evaluation through coordination meetings and integral report cards; (3) Positive impacts in the form of improving the quality of graduates who have strong faith, superior academic and non-academic achievements, and high independence, as well as increasing public trust in this institution. This educational model emphasizes the importance of a holistic approach to produce a generation with character and able to compete in the modern era.